Improvement of Combustion Process and Exhaust Emissions with Premixed Charge Compression Ignition - Azizul, Muhamad Asri; Qabli Osman, Muhammad Kashyaf; Khalid, Amir; Azman, Nurul Adina; Zulkifli, Abd Fathul Hakim; Jalani, Noor Hisham; Razali, Azahari (Journal of Automotive Powertrain and Transportation Technology, 2022)
Premixed Charge Compression Ignition (PCCI) is a combustion concept that is characterized by low temperature, partially premixed combustion using early injections, large ignition delays and high percentages of Exhaust Gas Recirculation. This review paper discusses the premixed charge compression ignition (PCCI) and the way to reduce the emissions. A promising low-emission combustion concept is used by the premixed charge compression ignition (PCCI). Air and exhaust gas before auto-ignition, the soot and NOx emissions are lower than for conventional diesel combustion by partially mixing the fuel. Fuel lean premixed combustion has potentials to achieve high efficiency and low emissions. The ignitability of lean mixture, flame stability and controlling in this combustion are significant issues to be addressed. The main issues for lean burn intermittent combustion engines are (i) the mixture preparation for lean combustion requires expensive or premium technology and (ii) achieving this combustion over a wide range of load and speed is difficult for a smooth-running engine.